Anticariogenic potencial of acidulate solutions with low fluoride concentration - Delbem, Alberto Carlos Botazzo [UNESP]; Tiano, Gilberto Carlos [UNESP]; Alves, Karina Mirela Riheiro Pinto [UNESP]; Cunha, Robson Frederico [UNESP] (Journal Of Applied Oral Science : Revista Fob, 2006)
Objetives: The aim of this study was to verify the anticariogenic effect of acidulate solutions with low NaF concentration, using pH-cycling model and bovine enamel. Material and methods: Enamel blocks were submitted to the surface microhardness (SMH) test and randomly divided in 12 experimental and one placebo groups. The blocks were submitted to pH cycling for 7 days, with daily applications once/day of 0.05% NaF and 0.1% NaF and twice/day of 0.02% NaF solutions. Four different pH: 4.0. 5.0, 6.0 and 7.0 were used. Next, SMH test was again used to determine the surface microhardness percentage change (%SMH). Data obtained for %SMH were homogeneous and passed through variance analyses and Tukey's test (5%) as far as fluoride concentrations and pH. Resulls:The results showed that pH influenced %SMH in 0.02% NaF and 0.05% NaF solutions with pH 4.0, which had less mineral loss compared to pH 7.0 (p̃0.05). The 0.02% NaF - pH 4.0, and 0.05% NaF- pH 7.0 groups showed similar results (p>0.05). A dose-response relationship was observed among the tested solutions, with better anticariogenic effect for the 0.1% NaF solution. Conclusion: The results suggest that the addition of citric acid to acidulate mouth rinses reduce mineral loss.

Objetivo: O objetivo do presente estudo foi verificar o efeito anticariogênico de soluções aciduladas com baixa concentração de flúor, usando um modelo de ciclagem de pH e esmalte bovino. Máterial e Método: Blocos de esmalte foram polidos, submetidos ao teste de microdureza de superfície (SMH) e divididos aleatoriamente em 12 grupos experimentais e um placebo. Os blocos foram submetidos à ciclagem de pH por 7 dias e a aplicações diárias de soluções de NaF a 0,05% e 0,1% (1x) e de 0,02% (2x), com pHs 4.0, 5.0, 6.0 e 7.0. A seguir, determinou-se a SMH novamente para o cálculo da porcentagem de alteração da microdureza de superfície (%SMH). Os dados de %SMH foram homogêneos e submetidos a análise de variância e teste de Tukey (5%) considerando as concentrações de flúor e pH. Resultados: O pH influenciou a %SMH nas soluções de NaF 0,02% e 0,05% com pH 4.0, no qual a perda mineral foi menor quando comparado ao pH 7.0 (p<0,05). Os grupos das soluções de NaF 0,02% - pH 4.0, e de NaF 0,05% - pH 7.0 mostraram resultados similares (p>0,05). A relação dose-resposta foi observada entre as soluções testadas, com melhor efeito anticariogênico para a solução de NaF 0,1%. Conclusão: Os resultados sugerem que a acidificação das soluções com baixa concentração de fluoreto reduz a perda mineral.
Potencial anticariogênico de soluções aciduladas com baixa concentração de flúor
Keywords: Administration & dosage; Dental caries; Dental enamel; Hardness; Prevention & control; Sodium fluoride